Plano de gerenciamento de resíduos de serviços de saúde na Maternidade Dr Augusto Sérgio Santos de Almeida em Tucuruí-PA - RODRIGUES, Karlla Jeannes Sousa (2022)
The inefficiency of solid waste management in a health service exposes the professionals involved in the hospital unit to biological and chemical risk agents and sharp materials, the environment and public health. Therefore, the objective of this study was to propose a Solid Waste Management Plan in a Health Service (PGRSS) at the Dr Augusto Sérgio Santos de Almeida maternity hospital in Tucuruí-PA, meeting the requirements of current legislation RDC 222/ 2018 and Conama 358/ 2005. The methodology used initially was a bibliographical research and later a case study was carried out, by systematic intensive direct observation, through a technical visit, photographic record and taking notes of the management steps, in addition to using a technical plant of the HMT provided by the Municipal Department of Works and Urbanism for the characterization of waste, which currently offers maternity services related to obstetrics, elective surgeries, ultrasounds and laboratory tests. The research results are intended to disseminate and suggest the Health Service Solid Waste Management Plan - PGRSS, urgently, through the diagnosis performed, contributing significantly and usefully to sustainable development in the hospital unit and compliance with environmental legislation current. The expectation generated is that the implementation of the PGRSS takes place and that the team is properly instructed through educational practices.